A new high-resolution chronology for the late Maastrichtian warming event: establishing robust temporal links with the onset of Deccan volcanism - Barnet, James S.K.; Littler, Kate; Kroon, Dick; Leng, Melanie J.; Westerhold, Thomas; Röhl, Ursula; Zachos, James C. (Geological Society of America, 2017)
The late Maastrichtian warming event was defined by a global temperature increase of ∼2.5–5 °C that occurred ∼150–300 k.y. before the Cretaceous-Paleogene (K-Pg) mass extinction. This transient warming event has traditionally been associated with a major pulse of Deccan Traps (west-central India) volcanism; however, large uncertainties associated with radiogenic dating methods have long hampered a definitive correlation. Here we present a new high-resolution, single species, benthic stable isotope record from the South Atlantic, calibrated to an updated orbitally tuned age model, to provide a revised chronology of the event, which we then correlate to the latest radiogenic dates of the main Deccan Traps eruption phases. Our data reveal that the initiation of deep-sea warming coincides, within uncertainty, with the onset of the main phase of Deccan volcanism, strongly suggesting a causal link. The onset of deep-sea warming is synchronous with a 405 k.y. eccentricity minimum, excluding a control by orbital forcing alone, although amplified carbon cycle sensitivity to orbital precession is evident during the greenhouse warming. A more precise understanding of Deccan-induced climate change paves the way for future work focusing on the fundamental role of these precursor climate shifts in the K-Pg mass extinction.